Deglaciation of Anticosti Island (eastern Canada) and its implications on climate-driven dynamics of the Laurentide Ice Sheet margin - Pierre-Olivier Couette; Pascal Bernatchez; Vincent Rinterknecht; Bernard Hétu; Jérôme Dubé; Patrick Lajeunesse (Quaternary Science Reviews, 2026)

The responsibility of Western European coastal states for the conservation of two emblematic migratory seabirds in the context of offshore wind farms - Alice Bernard; Nicolas Courbin; Jérémy Tornos; Tristan J.B. Martin; Mathilde Lejeune; Aurélien Prudor; Pascal Provost; Adrien Lambrechts; Chris P. Gaskin; Jérôme Cabelguen; Matthieu Bécot; Frédéric Jiguet; et al. (Biological Conservation, 2026)

Canopy Microclimate and Leaf Traits Shape Interspecies Variation in Photosynthetic Temperature Responses of Evergreen Tropical Trees in the Congo Basin - Thomas Sibret; Félicien Meunier; Kristine Y. Crous; Sarah Lamotte; Marc Peaucelle; Louise Terryn; Pieter De Frenne; Ivan Janssens; Bernard Bonyoma; Hans Verbeeck; Marijn Bauters; Pascal Boeckx (Global Change Biology, 2026)
Tropical forests contribute disproportionately to global carbon cycling, yet their resilience under climate warming remains uncertain, partly due to limited understanding of leaf‐level temperature responses of photosynthesis. In particular, the role of fine‐scale canopy microclimate in shaping photosynthetic temperature responses in tropical trees has been overlooked. We quantified vertical microclimate variation and measured leaf‐level photosynthetic temperature responses in 13 coexisting evergreen tree species spanning the full canopy profile in a lowland Congo Basin forest. Leaf gas exchange measurements were integrated with structural leaf traits and high‐resolution microclimate profiles to assess how temperature conditions and ecological strategies shape photosynthetic responses. Photosynthetic traits, including the light‐saturated photosynthetic rate at the temperature optimum and stomatal conductance at the temperature optimum, increased with canopy height, with pioneer species showing steeper increases than non‐pioneers. The temperature optimum of photosynthesis ( T opt ) was positively related to both mean and maximum leaf temperature ( T leaf ), driven mainly by interspecific differences rather than intraspecific plasticity. This suggests that T opt reflects species‐level adaptation to the temperature conditions of their canopy niche rather than leaf‐level adjustment to local microclimate. Stomatal conductance influenced T leaf via transpiration and thereby contributed to shaping T opt . Leaves experiencing larger temperature fluctuations showed reduced sensitivity, reflected in a broader photosynthetic temperature‐response width ( Ω ). Ω was also positively associated with structural traits such as leaf mass per area and leaf dry matter content, both within and among species, indicating that greater structural investment helps sustain higher photosynthetic rates across wider temperature ranges and enhances tolerance to temperature variability. By linking canopy microclimate, physiological traits, and structural characteristics, our findings demonstrate how vertical microclimatic gradients and functional diversity jointly determine photosynthetic temperature responses in tropical forest trees. Incorporating leaf‐level temperature regimes, stomatal regulation, and trait variation into vegetation models could improve predictions of tropical forest carbon dynamics under climate change.

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

No impact of black-eye symptom on foraging behaviour and reproductive success of Northern gannets following highly pathogenic avian influenza - Aurore Ponchon; Pascal Provost; Alice Bernard; Thierry Boulinier; Mathilde Lejeune; Amélie Lescroël; Jérémy Tornos; David Grémillet (Biological Conservation, 2026)

The dithiocarbamate pesticides maneb and mancozeb disturb the metabolism of lipids and xenobiotics in an in vitro model of metabolic dysfunction-associated steatotic liver disease - Kilian Petitjean; Giovanna Dicara; Sébastien Bristeau; Hugo Coppens-Exandier; Laurence Amalric; Nicole Baran; Camille C. Savary; Anne Corlu; Pascal Loyer; Bernard Fromenty (Environmental Toxicology and Pharmacology, 2025)

Effects of agricultural terraces on landslide occurrence: Insights from a tropical mountainous region (Rwanda, Africa) - Pascal Sibomana; Matthias Vanmaercke; Arthur Depicker; Bernard Tychon; Aurélia Hubert; Olivier Dewitte (CATENA, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Bonobo (Pan paniscus) Density and Distribution in Central Africa's Largest Rainforest Reserve: Long-term Survey Data Show Pitfalls in Methodological Approaches and Call for Vigilance - Mattia Bessone; Hjalmar S. Kühl; Ilka Herbinger; Gottfried Hohmann; Kouamé Paul N’Goran; Papy Asanzi; Stephen Blake; Michel Basele; Martin Bofeko; Nono Bondjengo; Pitshou Wangongo Bondo; Rigobert Booto; et al. (International Journal of Primatology, 2025)
Conservation measures require accurate estimates of density and abundance and population trend assessments. The bonobo ( Pan paniscus ) is considered Endangered in the IUCN Red List. This classification assumes that available population data are representative. However, with only 30% of the bonobo’s historic geographical range surveyed, reliable information is needed to assess the species' population status. Here, we use information from 13 surveys conducted between 2002 and 2018 in an area of 42,000 km 2 , representing ~27% of bonobo-suitable habitat: Salonga National Park and its corridor, Democratic Republic of the Congo (DRC). Using 8310 km of reconnaissance and transect walks and 27,045 days of camera trapping, we: (1) provide updated estimates of bonobo population density and distribution (42,000 km 2 ; ~5,000 km 2 of which, to the best of our knowledge, have not been surveyed before by scientists), (2) assess population trends (15,758 km 2 ; 2002–2008 vs 2012–2018), (3) compare estimates obtained with different methods, and (4) assess the factors driving bonobo density and distribution. Although we detected a non-significant population decline, our study suggests that Salonga is a bonobo stronghold, with a population ranging between 8244 and 18,308 mature individuals (density: 0.31 individuals/km 2 ). Standing crop nest counts returned non-significantly lower density estimates than camera trap distance sampling. Nest count-estimates were higher in areas with Marantaceae understorey and those farther away from rivers, while camera trap-estimates were higher in areas with lower human presence. Regardless of the method, bonobos were rarer in proximity to villages. They occurred more often in areas of dense forest cover and in proximity to ranger posts. Our results point towards a declining bonobo population in Salonga, but do not provide sufficient evidence to confirm this statistically. Consequently, the continued monitoring of the bonobo population and preservation of the integrity of Salonga, considering its biological and cultural heritage, will be crucial in the preservation of this stronghold of wild bonobos.

Weeding force saving to improve profitability of cassava-legumes cropping systems in eastern Democratic Republic of the Congo - Audry Muke; Leon Nabahungu; Kokou Kinché; Bernard Vanlauwe; Pascal Boeckx (Crop Protection, 2025)

Reading tea leaves worldwide: Decoupled drivers of initial litter decomposition mass‐loss rate and stabilization - Judith M. Sarneel; Mariet M. Hefting; Taru Sandén; Johan van den Hoogen; Devin Routh; Bhupendra S. Adhikari; Juha M. Alatalo; Alla Aleksanyan; Inge H. J. Althuizen; Mohammed H. S. A. Alsafran; Jeff W. Atkins; Laurent Augusto; et al. (Ecology Letters, 2024)
The breakdown of plant material fuels soil functioning and biodiversity. Currently, process understanding of global decomposition patterns and the drivers of such patterns are hampered by the lack of coherent large‐scale datasets. We buried 36,000 individual litterbags (tea bags) worldwide and found an overall negative correlation between initial mass‐loss rates and stabilization factors of plant‐derived carbon, using the Tea Bag Index (TBI). The stabilization factor quantifies the degree to which easy‐to‐degrade components accumulate during early‐stage decomposition (e.g. by environmental limitations). However, agriculture and an interaction between moisture and temperature led to a decoupling between initial mass‐loss rates and stabilization, notably in colder locations. Using TBI improved mass‐loss estimates of natural litter compared to models that ignored stabilization. Ignoring the transformation of dead plant material to more recalcitrant substances during early‐stage decomposition, and the environmental control of this transformation, could overestimate carbon losses during early decomposition in carbon cycle models.

X-ray tomography applied to tsunami deposits: Optimized image processing and quantitative analysis of particle size, particle shape, and sedimentary fabric in 3D - Saptarshee Mitra; Raphaël Paris; Laurent Bernard; Rémi Abbal; Pascal Charrier; Simon Falvard; Pedro Costa; César Andrade (Marine Geology, 2024)

Low concentrations of ethylene bisdithiocarbamate pesticides maneb and mancozeb impair manganese and zinc homeostasis to induce oxidative stress and caspase-dependent apoptosis in human hepatocytes - Kilian Petitjean; Yann Verres; Sébastien Bristeau; Catherine Ribault; Caroline Aninat; Christophe Olivier; Patricia Leroyer; Martine Ropert; Olivier Loréal; Olivier Herault; Laurence Amalric; Nicole Baran; et al. (Chemosphere, 2024)

First Records of a Hydrolagus Species (Holocephali: Chimaeridae) from Reunion Island and Mayotte (Southwestern Indian Ocean) - Bernard Séret; Jean-Pascal Quod (Fishes, 2023)
Two specimens of large blackish chimaeras of the genus Hydrolagus were caught, one off Reunion Island and the other off Mayotte in the southwestern Indian Ocean. The specimens, an adult male of 710 mm BDL and a female of 870 m BDL, are described, compared to similar species (i.e., having a large size, over 110 cm TL, dark blackish colour, and rather long conical snout), and tentatively identified to the small-eyed rabbitfish Hydrolagus affinis, pending a taxonomic revision of the large blackish chimaeras is completed.

Strong breeding colony fidelity in northern gannets following high pathogenicity avian influenza virus (HPAIV) outbreak - David Grémillet; Aurore Ponchon; Pascal Provost; Amandine Gamble; Mouna Abed-Zahar; Alice Bernard; Nicolas Courbin; Grégoire Delavaud; Armel Deniau; Jérôme Fort; Keith C. Hamer; Ruth Jeavons; et al. (Biological Conservation, 2023)

The 2020–2021 seismic sequence in the Western Gulf of Corinth: Insights on the triggering mechanisms through high resolution seismological and geodetic data analysis - Anna Serpetsidaki; Vasilis Kapetanidis; Panagiotis Elias; Alexis Rigo; Ioannis Spingos; Louis De Barros; Olivier Lengliné; Simon Bufféral; Andreas Karakonstantis; Pascal Bernard; Pierre Briole; Jiří Zahradník; et al. (Tectonophysics, 2023)

Correction to: Vegetation attributes drive the taxonomic richness and functional composition of beetles and spiders in mountainous urban green spaces - Frederick Gyasi Damptey; Bernard Fosu Frimpong; Daniel Kwame Debrah; Prince Pascal Agro; Edward Debrah Wiafe (Energy, Ecology and Environment, 2023)

Vegetation attributes drive the taxonomic richness and functional composition of beetles and spiders in mountainous urban green spaces - Frederick Gyasi Damptey; Bernard Fosu Frimpong; Daniel Kwame Debrah; Prince Pascal Agro; Edward Debrah Wiafe (Energy, Ecology and Environment, 2022)
Urban green spaces (UGS) enhance the quality of life in urban environments and serve as habitat corridors or refuge for organisms, including beetles and spiders. The attributes of UGS allow them to harbour species that offer essential ecosystem services. However, the ability of UGS to provide services is limited by the extent to which they have been altered anthropogenically. We described the taxonomic richness and functional composition of arthropods in a mountainous urban ecosystem of Ghana by focussing on the activity of both beetles and spiders at the family level. Two main land-use types (woodlands and built-up areas) were identified and characterised based on the presence or absence of certain vegetation attributes. Sixteen plots in each land-use type with sizes 20 × 20 m were demarcated and fitted with four pitfall traps in each plot to sample continuously for eight weeks, the activity density of both beetles and spiders. Samples were sorted into families and functional groups (detritivores, fungivores, herbivores and predators). The taxonomic richness and activity density were both significantly higher in the woodlands than in the built-up areas. Similarly, all functional groups showed a higher affinity to the woodlands than the built-up areas. Habitat attributes defined by plant diversity and structural complexity were the underlying drivers explaining the differences in arthropod communities between the land-use types. Though the built-up areas seem degraded and open, the remaining small vegetation patches still support the activities of some taxa that should merit the protection of such remnant vegetation in urban ecosystems.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Mechanism of Cellular Formation and In Vivo Seeding Effects of Hexameric β-Amyloid Assemblies - Céline Vrancx; Devkee M. Vadukul; Nuria Suelves; Sabrina Contino; Ludovic D’Auria; Florian Perrin; Vincent van Pesch; Bernard Hanseeuw; Loïc Quinton; Pascal Kienlen-Campard (Molecular Neurobiology, 2021)
The β-amyloid peptide (Aβ) is found as amyloid fibrils in senile plaques, a typical hallmark of Alzheimer’s disease (AD). However, intermediate soluble oligomers of Aβ are now recognized as initiators of the pathogenic cascade leading to AD. Studies using recombinant Aβ have shown that hexameric Aβ in particular acts as a critical nucleus for Aβ self-assembly. We recently isolated hexameric Aβ assemblies from a cellular model, and demonstrated their ability to enhance Aβ aggregation in vitro. Here, we report the presence of similar hexameric-like Aβ assemblies across several cellular models, including neuronal-like cell lines. In order to better understand how they are produced in a cellular context, we investigated the role of presenilin-1 (PS1) and presenilin-2 (PS2) in their formation. PS1 and PS2 are the catalytic subunits of the γ-secretase complex that generates Aβ. Using CRISPR-Cas9 to knockdown each of the two presenilins in neuronal-like cell lines, we observed a direct link between the PS2-dependent processing pathway and the release of hexameric-like Aβ assemblies in extracellular vesicles. Further, we assessed the contribution of hexameric Aβ to the development of amyloid pathology. We report the early presence of hexameric-like Aβ assemblies in both transgenic mice brains exhibiting human Aβ pathology and in the cerebrospinal fluid of AD patients, suggesting hexameric Aβ as a potential early AD biomarker. Finally, cell-derived hexameric Aβ was found to seed other human Aβ forms, resulting in the aggravation of amyloid deposition in vivo and neuronal toxicity in vitro.

COVID-19 or not COVID-19? Compared characteristics of patients hospitalized for suspected COVID-19 - Thomas Rogier; Isabelle Eberl; Florian Moretto; Thibault Sixt; François-Xavier Catherine; Clémentine Estève; Maroua Abdallahoui; Lucile Behague; Antoine Coussement; Lucas Mathey; Sophie Mahy; Marielle Buisson; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Physico-chemical soil attributes under conservation agriculture and integrated soil fertility management - Eunice A. Mutuku; Bernard Vanlauwe; Dries Roobroeck; Pascal Boeckx; Wim M. Cornelis (Nutrient Cycling in Agroecosystems, 2021)

The GenTree Leaf Collection: Inter‐ and intraspecific leaf variation in seven forest tree species in Europe - Raquel Benavides; Bárbara Carvalho; Cristina C. Bastias; David López‐Quiroga; Antonio Mas; Stephen Cavers; Alan Gray; Audrey Albet; Ricardo Alía; Olivier Ambrosio; Filippos Aravanopoulos; Francisco Auñón; et al. (Global Ecology and Biogeography, 2021)
Motivation Trait variation within species can reveal plastic and/or genetic responses to environmental gradients, and may indicate where local adaptation has occurred. Here, we present a dataset of rangewide variation in leaf traits from seven of the most ecologically and economically important tree species in Europe. Sample collection and trait assessment are embedded in the GenTree project (EU‐Horizon 2020), which aims at characterizing the genetic and phenotypic variability of forest tree species to optimize the management and sustainable use of forest genetic resources. Our dataset captures substantial intra‐ and interspecific leaf phenotypic variability, and provides valuable information for studying the relationship between ecosystem functioning and trait variability of individuals, and the response and resilience of species to environmental changes. Main types of variable contained We chose morphological and chemical characters linked to trade‐offs between acquisition and conservation of resources and water use, namely specific leaf area, leaf size, carbon and nitrogen content and their ratio, and the isotopic signature of stable isotope 13 C and 15 N in leaves. Spatial location and grain We surveyed between 18 and 22 populations per species, 141 in total, across Europe. Time period Leaf sampling took place between 2016 and 2017. Major taxa and level of measurement We sampled at least 25 individuals in each population, 3,569 trees in total, and measured traits in 35,755 leaves from seven European tree species, i.e. the conifers Picea abies , Pinus pinaster and Pinus sylvestris , and the broadleaves Betula pendula , Fagus sylvatica , Populus nigra and Quercus petraea . Software format The data files are in ASCII text, tab delimited, not compressed.

Spatial Distributions of Surface Sedimentary Organics and Sediment Profile Image Characteristics in a High-Energy Temperate Marine RiOMar: The West Gironde Mud Patch - Bastien Lamarque; Bruno Deflandre; Adriana Galindo Dalto; Sabine Schmidt; Alicia Romero-Ramirez; Frédéric Garabetian; Nicolas Dubosq; Mélanie Diaz; Florent Grasso; Aldo Sottolichio; Guillaume Bernard; Hervé Gillet; et al. (Journal of Marine Science and Engineering, 2021)
The spatial distributions of (1) surface sediment characteristics (D0.5, Sediment Surface Area (SSA), Particulate Organic Carbon (POC), Chlorophyll-a (Chl-a), Phaeophytin-a (Phaeo-a), Total and Enzymatically Hydrolyzable Amino Acids (THAA, EHAA), δ13C) and (2) sediment profile image (apparent Redox Potential Discontinuity (aRPD), numbers and depths of biological traces) characteristics were quantified based on the sampling of 32 stations located within the West Gironde Mud Patch (Bay of Biscay, NE Atlantic) in view of (1) assessing the spatial structuration of a temperate river-dominated ocean margin located in a high-energy area, (2) disentangling the impacts of hydrodynamics and bottom trawling on this structuration, and (3) comparing the West Gironde Mud Patch with the Rhône River Prodelta (located in a low-energy area). Results support the subdivision of the West Gironde Mud Patch in a proximal and a distal part and show (1) the existence of depth gradients in surface sedimentary organics characteristics and bioturbation within the distal part; (2) no evidence for a significant effect of bottom trawling, as opposed to Bottom Shear Stress, on the West Gironde Mud Patch spatial structuration; and (3) major discrepancies between spatial structuration in the West Gironde Mud Patch and the Rhône River Prodelta, which were attributed to differences in tidal regimes, sedimentation processes, and local hydrodynamics, which is in agreement with current river-dominated ocean margin typologies.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Intensive targeting of regulatory competence genes by transposable elements in streptococci - Maud Fléchard; Céline Lucchetti-Miganeh; Bernard Hallet; Pascal Hols; Philippe Gilot (Molecular Genetics and Genomics, 2019)

Paleoclimate variations and impact on groundwater recharge in multi-layer aquifer systems using a multi-tracer approach (northern Aquitaine basin, France) - Marc Saltel; Romain Rebeix; Bertrand Thomas; Michel Franceschi; Bernard Lavielle; Pascal Bertran (Hydrogeology Journal, 2019)

Impact of Geological Heterogeneities on Induced-Seismicity in a Deep Sublevel Stoping Mine - Francesca De Santis; Isabelle Contrucci; Jannes Kinscher; Pascal Bernard; Vincent Renaud; Yann Gunzburger (Pure and Applied Geophysics, 2019)

Aseismic Mining Subsidence in an Abandoned Mine: Influence Factors and Consequences for Post-Mining Risk Management - Isabelle Contrucci; Cyrille Balland; Jannes Kinscher; Mustapha Bennani; Pascal Bigarré; Pascal Bernard (Pure and Applied Geophysics, 2019)

Nest design in a changing world: Great tit Parus major nests from a Mediterranean city environment as a case study - Marcel M. Lambrechts; Anne Charmantier; Virginie Demeyrier; Annick Lucas; Samuel Perret; Matthieu Abouladzé; Michel Bonnet; Coline Canonne; Virginie Faucon; Stéphanie Grosset; Gaëlle le Prado; Frédéric Lidon; et al. (Urban Ecosystems, 2017)

Phosphorus availability and microbial community in the rhizosphere of intercropped cereal and legume along a P-fertilizer gradient - Xiaoyan Tang; Sarah A. Placella; Florent Daydé; Laetitia Bernard; Agnès Robin; Etienne-Pascal Journet; Eric Justes; Philippe Hinsinger (Plant and Soil, 2016)

Calcium signals inhibition sensitizes ovarian carcinoma cells to anti-Bcl-xL strategies through Mcl-1 down-regulation - Marie-Laure Bonnefond; Bernard Lambert; Florence Giffard; Edwige Abeilard; Emilie Brotin; Marie-Hélène Louis; Mor Sény Gueye; Pascal Gauduchon; Laurent Poulain; Monique N’Diaye (Apoptosis, 2015)

Heart failure prognosis and management in over-80-year-old patients: data from a French national observational retrospective cohort - Charles Vorilhon; Chouki Chenaf; Aurélien Mulliez; Bruno Pereira; Guillaume Clerfond; Nicolas Authier; Frédéric Jean; Pascal Motreff; Bernard Citron; Alain Eschalier; Jean-R Lusson; Romain Eschalier (European Journal of Clinical Pharmacology, 2015)

Comparative genomic analysis provides insights into the evolution and niche adaptation of marine M agnetospira sp. QH ‐2 strain - Boyang Ji; Sheng‐Da Zhang; Pascal Arnoux; Zoe Rouy; François Alberto; Nadège Philippe; Dorothée Murat; Wei‐Jia Zhang; Jean‐Baptiste Rioux; Nicolas Ginet; Monique Sabaty; Sophie Mangenot; et al. (Environmental Microbiology, 2014)
Summary Magnetotactic bacteria ( MTB ) are capable of synthesizing intracellular organelles, the magnetosomes, that are membrane‐bounded magnetite or greigite crystals arranged in chains. Although MTB are widely spread in various ecosystems, few axenic cultures are available, and only freshwater M agnetospirillum spp. have been genetically analysed. Here, we present the complete genome sequence of a marine magnetotactic spirillum, M agnetospira sp. QH ‐2. The high number of repeats and transposable elements account for the differences in QH ‐2 genome structure compared with other relatives. Gene cluster synteny and gene correlation analyses indicate that the insertion of the magnetosome island in the QH ‐2 genome occurred after divergence between freshwater and marine magnetospirilla. The presence of a sodium‐quinone reductase, sodium transporters and other functional genes are evidence of the adaptive evolution of M agnetospira sp. QH ‐2 to the marine ecosystem. Genes well conserved among freshwater magnetospirilla for nitrogen fixation and assimilatory nitrate respiration are absent from the QH ‐2 genome. Unlike freshwater M agnetospirillum spp., marine M agnetospira sp. QH ‐2 neither has TonB and TonB ‐dependent receptors nor does it grow on trace amounts of iron. Taken together, our results show a distinct, adaptive evolution of M agnetospira sp. QH ‐2 to marine sediments in comparison with its closely related freshwater counterparts.

Human proximity and habitat fragmentation are key drivers of the rangewide bonobo distribution - Jena R. Hickey; Janet Nackoney; Nathan P. Nibbelink; Stephen Blake; Aime Bonyenge; Sally Coxe; Jef Dupain; Maurice Emetshu; Takeshi Furuichi; Falk Grossmann; Patrick Guislain; John Hart; et al. (Biodiversity and Conservation, 2013)

Field experiment in Soultz-sous-Forêts, 1993: Changes of the pattern of induced seismicity - Vladimir Smirnov; Alexander Ponomarev; Pascal Bernard; Seid Bourouis (Acta Geophysica, 2013)

Mid‐century effects of Climate Change on African monsoon dynamics using the A1B emission scenario - Paul‐Arthur Monerie; Pascal Roucou; Bernard Fontaine (International Journal of Climatology, 2013)
Future climate changes in African regions are model‐dependent and there is no consensus regarding Sahelian rainfall by the end of this century. Using 12 atmosphere‐ocean global climate models of the third Coupled Model Intercomparison Project (CMIP3) we propose a multi‐model (MM) analysis contrasting the 1960–1999 period (20c3m integration) and the 2031–2070 period (A1B emission scenario). The analyses are based on MM response but also on the ‘one model‐one vote’ concept to give the same weight to each model. The results show robust signals in the rainfall response, i.e., increasing (decreasing) amounts in central (western) Sahel associated with specific changes in atmospheric dynamics. The rainfall excesses expected in central Sahel are mainly linked to an enhancement of the northern Hadley‐type cell and probably to its northward shift. At low‐levels increasing temperature and evaporation strengthen the monsoon flux. Rainfall deficits predicted westward are due to a reinforcement of the African Easterly Jet and to anomalies in the zonal circulation between the Indian and the Atlantic Oceans, favouring air subsidence and moisture export outside the region. The weakening of the meridional circulation is also able to prevent rainfall amounts in the western part of the Sahel. More generally, these analyses show that in future works the Sahel region must not be considered as one consistent region but as two separate areas, both sides of the Greenwich meridian. The authors propose to consider this feature in the next Fifth Assessment cycle (AR5) in order to better understand the impacts of the climate change on West Africa. Copyright © 2012 Royal Meteorological Society

Identification of mediator complex 26 (Crsp7) gametologs on platypus X1 and Y5 sex chromosomes: a candidate testis-determining gene in monotremes? - Enkhjargal Tsend-Ayush; R. Daniel Kortschak; Pascal Bernard; Shu Ly Lim; Janelle Ryan; Ruben Rosenkranz; Tatiana Borodina; Juliane C. Dohm; Heinz Himmelbauer; Vincent R. Harley; Frank Grützner (Chromosome Research, 2012)

Sox9 gene regulation and the loss of the XY/XX sex-determining mechanism in the mole vole Ellobius lutescens - Stefan Bagheri-Fam; Rajini Sreenivasan; Pascal Bernard; Kevin C. Knower; Ryohei Sekido; Robin Lovell-Badge; Walter Just; Vincent R. Harley (Chromosome Research, 2012)

Aphid-host plant interactions: does aphid honeydew exactly reflect the host plant amino acid composition? - Pascal D. Leroy; Bernard Wathelet; Ahmed Sabri; Frédéric Francis; François J. Verheggen; Quentin Capella; Philippe Thonart; Eric Haubruge (Arthropod-Plant Interactions, 2011)

Recent changes in precipitation, ITCZ convection and northern tropical circulation over North Africa (1979–2007) - Bernard Fontaine; Pascal Roucou; Marco Gaetani; Romain Marteau (International Journal of Climatology, 2011)
This article focuses on some recent changes observed in the Tropics with special emphasis on the African monsoon region using high‐resolution gridded precipitation from the Climatic Research Unit (period 1979–2002), outgoing longwave radiation at the top of the atmosphere from the National Oceanic and Atmospheric Administration and atmospheric reanalyses from the Climate Prediction Center (NCEP‐DOE2, period 1979–2007). The results show a rainfall increase in North Africa since the mid‐90s with significant northward migrations of rainfall amounts, i.e. + 1.5° for the 400 mm July to September isohyets, whereas deep convection has significantly increased and shifted northward. The subsidence branch of the northern meridional overturning has also been reinforced and shifted by 1° latitude northward in winter. At larger scale, an unambiguous reorganisation of the circulation with increasing subsidence in high troposphere over the Mediterranean and increasing ascendance in the African Intertropical Convergence Zone in northern summer has been noticed in the meridional cell overturning. After 1993–1994, the migration of the Saharan heat low towards northwest has been more marked (+1° to + 2° in latitude; − 1° to − 2° in longitude), whereas its centre intensified at the peak of the tropical rainy season (+10 gpm thickness in the 700–925 hPa layer). These changes are associated with significant reinforcements of the southwesterly low‐level winds and Tropical Easterly jet and with a northward shift of the African Easterly jet. Analyses of Global Circulation Model outputs issued from Intergovernmental Panel on Climate Change (A1B scenario and from forced experiments on the ARPEGE‐climat (Action de Recherche Petite Echelle Grande Echelle) and Atmospheric Global Circulation Model show that at least part of these changes could be due to the recent warming observed in the Mediterranean/Saharan region. Copyright © 2010 Royal Meteorological Society

Impacts of warm and cold situations in the Mediterranean basins on the West African monsoon: observed connection patterns (1979–2006) and climate simulations - Bernard Fontaine; Javier Garcia-Serrano; Pascal Roucou; Belen Rodriguez-Fonseca; Teresa Losada; Fabrice Chauvin; Sébastien Gervois; Sivarajan Sijikumar; Paolo Ruti; Serge Janicot (Climate Dynamics, 2010)

French cohort of the uranium processing workers: mortality pattern after 30-year follow-up - Irina Guseva Canu; Elisabeth Cardis; Camille Metz-Flamant; Sylvaine Caër-Lorho; Bernard Auriol; Pascal Wild; Dominique Laurier; Margot Tirmarche (International Archives of Occupational and Environmental Health, 2010)

Comparative analysis of reproductive traits in 65 freshwater fish species: application to the domestication of new fish species - Fabrice Teletchea; Alexis Fostier; Ewa Kamler; Jean-Noël Gardeur; Pierre-Yves Le Bail; Bernard Jalabert; Pascal Fontaine (Reviews in Fish Biology and Fisheries, 2009)

Definition and predictability of an OLR‐based West African monsoon onset - Bernard Fontaine; Samuel Louvet; Pascal Roucou (International Journal of Climatology, 2008)
The monsoon onset is documented in terms of latitudinal shift of deep convection areas within the ITCZ using an interpolated version of the National Oceanic and Atmospheric Administration (NOAA) Outgoing Longwave Radiation (OLR) at a 5‐day time‐step over West Africa for the period 1979–2004. Signals in moist convection derived from OLR values lower than 180 W/m2 allow better determination of onset dates (ODs) than the use of other thresholds or of the raw values of OLR. Such ODs are defined without any time filtering or spatial averaging along the meridional plane. They are also significantly correlated with ODs based on other datasets such as the CMAP and Global Precipitation Climatology Project (GPCP) rainfall estimates, and seem more realistic, especially during years when the latitudinal shift is unclear and delayed. However, the respective means [30 June for ODs based on OLR ( vs ) 25 June for ODs based on CMAP and GPCP] and standard deviations [15.6 ( vs ) 8.1 days] are slightly different. These differences illustrate the fact that the monsoon onset corresponds to a 10–15‐day transition in the West African monsoon seasonal evolution which does not affect, concomitantly, all variables describing the system. The onset is clearly linked to the time evolution of a few key‐descriptors of the monsoon system at regional scale such as the installation of northward meridional gradients of moist static energy in low levels and of the monsoon cell over the continent. It is also associated with specific variations of the relative vorticity in low troposphere and of the velocity potential in upper levels over the Sahel region. Moreover, OD time series exhibits good predictability. Multivariate linear regressions have been performed in a leave‐one‐out cross‐validation way using OLR and selected atmospheric predictors in May. The best results explain 60% of the OD variance and are obtained with 2 types of predictors: the OLR gradients between the Gulf of Guinea and the African continent, and the northward migration of the West African Monsoon cell. Copyright © 2008 Royal Meteorological Society

Use of principal component analysis to assess factors controlling net N mineralization in deciduous and coniferous forest soils - Hilde Vervaet; Bernard Massart; Pascal Boeckx; Oswald Van Cleemput; Georges Hofman (Biology and Fertility of Soils, 2002)

Impact of Multiple Insertions of two Retroelements, ZAM and Idefix at an Euchromatic Locus - Caroline Conte; Valérie Calco; Sophie Desset; Pascal Leblanc; Bernard Dastugue; Chantal Vaury (Genetica, 2000)

Biosorption of cobalt by Pseudomonas halodentrificans: influence of cell wall treatment by alkali and alkaline-earth metals and ion-exchange mechanisms - Pascal Ginisty; Bernard Besnainou; Claire Sahut; Jean Guezennec (Biotechnology Letters, 1998)

Erythrocytes participate significantly in blood transport of amino acids during the post absorptive state in normal humans - Abdel-Nacer Agli; Adrien Schaefer; Bernard Geny; Franois Piquard; Pascal Haberey (European Journal of Applied Physiology, 1998)

Energetics of swelling in isolated hepatocytes: A comprehensive study - Anne Devin; Pascal Espié; Bernard Guérin; Michel Rigoulet (Molecular and Cellular Biochemistry, 1998)

A QTL with major effect on milk yield and composition maps to bovine Chromosome 14 - Wouter Coppieters; Juliette Riquet; Juan-José Arranz; Paulette Berzi; Nadine Cambisano; Bernard Grisart; Latifa Karim; Fabienne Marcq; Laurence Moreau; Carine Nezer; Patricia Simon; Pascal Vanmanshoven; et al. (Mammalian Genome, 1998)

Biological components from the Seine estuary: first results - Pascal Mouny; Jean Claude Dauvin; Christophe Bessineton; Bernard Elkaim; Serge Simon (Hydrobiologia, 1998)

VERTICAL MOTION CHANGES RELATED TO NORTH-EAST BRAZIL RAINFALL VARIABILITY: A GCM SIMULATION - PASCAL ROUCOU; JOSÉ ORIBE ROCHA DE ARAGÃO; ALI HARZALLAH; BERNARD FONTAINE; SERGE JANICOT (International Journal of Climatology, 1996)